Potential distribution of large mammals in the W National Park in Niger - (:unkn) unknown (My University, 2003)
The countries of West Africa protects numerous areas with a diversified fauna. But, especially on large mammals, few studies about wildlife have been performed contrarily to eastern and southern Africa where several research programs have been led for thirty years. Niger, hosts one of the oldest African fauna reserve: the W National Park. In order to allow managers to set a management policy to maintain, and even raise, the biodiversity, we developed a distribution analysis and rating method of large mammals. This method, called SAGEDOC (Spatial Analysis GEoreferenced Data Of Counts), takes into account the usually limited financial and logistic potentialities at managers disposal. The SAGEDOC method, using GIS potentialities (as space management tool) associated to contributions of remote sensing and multivariate statistics, is based on spatialised information permitting to understand the distribution of large mammals in dry season. Wildlife was considered as the central element of a geosystem which ecological and anthropic factors have various influences according to space and time. By considering this spatio-temporal variability, we could have pointed out the distribution of a great number of mammal species, socio-ecological characteristics of which are often very different.
Keywords: African Research